Public spending on health care in Africa: do the poor benefit? - F Castro-Leal; J Dayton; L Demery
Health care is a basic service essential in any effort to combat poverty, and is often subsidized with public funds to help achieve that aim. This paper examines public spending on curative health care in several African countries and finds that this spending favours mostly the better-off rather than the poor. It concludes that this targeting problem cannot be solved simply by adjusting the subsidy allocations. The constraints that prevent the poor from taking advantage of these services must also be addressed if the public subsidies are to be effective in reaching the poor